Eschatology and Eucharist: some Notes for a Sacramental Eschatology - Uríbarri Bilbao SJ, Gabino (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Eschatology and Eucharist illuminate one another. Cullman’s scheme «already – not yet» is analyzed in this paper, showing its inadequacy to express neither the presence of the grace in the Eucharist nor how the Kingdom of God breaks into history. Christian eschatology is better understood from a sacramental approach. This approach departs from a lineal understanding of time; expressing in a better way the newness of the event of Christ’s death and resurrection, and our present belonging to him; and allowing for the hope of the coming fullness. Christian eschatology is a sacramental eschatology.
Keywords: eschatology; Eucharist; already; not yet; kingdom of God; sacraments